2012
DOI: 10.1134/s0362119712020119
|View full text |Cite
|
Sign up to set email alerts
|

Blood serum concentration of lipids and lipoproteins and body composition

Abstract: The goal of this study was to analyze the relationship of the blood serum apolipoprotein E (apoE), total cholesterol (TC), triglycerides (TG), and high and low density lipoproteins (HDLP, LDLP) levels with the body mass index (BMI), relative body surface area (RBSA), and the body muscle (BM) and body fat (BF) amounts. The study was carried out in male and female subjects aged 14-16 years (adolescent age group 1: n 1 M = 141, n 1 F = 151) and 18-25 years (young adult group 2: n 2 M = 141, n 2 F =46). No signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Based on multivariate linear regression modeling, factors associated significantly and independently with serum lipid concentrations and their decreases during six-months of follow-up included higher BMI, older current age, and diagnosis of BD (Table 3), whereas higher serum lipid and glucose concentrations with older age would be expected [17,28,29]. As already noted, the association of obesity with BD may reflect risks associated with the disorder itself, with its often complex and sometimes unsatisfactory treatment, or, very likely, both [5,7,11,24].…”
Section: Discussionmentioning
confidence: 99%
“…Based on multivariate linear regression modeling, factors associated significantly and independently with serum lipid concentrations and their decreases during six-months of follow-up included higher BMI, older current age, and diagnosis of BD (Table 3), whereas higher serum lipid and glucose concentrations with older age would be expected [17,28,29]. As already noted, the association of obesity with BD may reflect risks associated with the disorder itself, with its often complex and sometimes unsatisfactory treatment, or, very likely, both [5,7,11,24].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from lipid metabolism, the Apo-E protein is thought to have a variety of functions, such as repairing blood vessel walls, regulation of immune status, and anti-oxidant activities. 28 The increase in serum levels of Apo-E in this study may have been in response to the increase in cholesterol levels. It may also have been increased in response to other factors, such as oxidative stress, mechanical stress on the blood vessel walls due to the type of exposure mode used (intravenous), and immune response.…”
Section: Dpv Injection Of Ni Nanoparticles Induced Liver Injurymentioning
confidence: 92%
“…According to A.I. Kozlov et al, low calcidiol concentration (below 50 nmol/l) was observed in 47% of the examined adolescents in the Perm Territory; deficient concentration of vitamin D was observed in 86% of the girls and boys in the Komi Republic in autumn and in 98% -in the early spring [25]. Thus, analysis of the level of children's and adolescent's provision with vitamin D in various climate/geographic regions of Russia indicates its differences and appears extremely important.…”
mentioning
confidence: 95%